2021
DOI: 10.1016/j.oooo.2020.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lymphovascular invasion in oral squamous cell carcinoma: A meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 56 publications
(60 reference statements)
2
40
1
Order By: Relevance
“…As an essential step in tumor metastasis, LVI has been considered a prognostic marker for poor prognosis in patients with OSCC ( 57 ). In the current meta-analysis of 30 studies for OS (30,481 samples), 30 studies for DFS (8,187 samples), and 13 for DSS (4,411 samples), we confirmed the significant prognostic role of LVI for OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…As an essential step in tumor metastasis, LVI has been considered a prognostic marker for poor prognosis in patients with OSCC ( 57 ). In the current meta-analysis of 30 studies for OS (30,481 samples), 30 studies for DFS (8,187 samples), and 13 for DSS (4,411 samples), we confirmed the significant prognostic role of LVI for OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients were divided into nodal-negative and -positive groups, with predictive models established separately for each group. In addition to the shortened interval of locoregional control, other independent factors were related to cancer metastasis, such as age, surgical margin, and lymphovascular invasion status ( 30 32 ). In the nodal-negative group, although only 5.4% (25/459) of the patients developed DM during the follow-up period, most (77.1% [459/595]) of the patients with OCSCC were in this group, and this first predictive model was established for them.…”
Section: Discussionmentioning
confidence: 99%
“….However younger crowd is showing more inclination towards OSCC nowadays. Therefore potential valuable markers in OSCC must be discovered for risk evaluation [1]. Researchers had studied metastatic invasive prognosticators histopathologically-Perineural invasion, Vascular invasion, Lymph node invasion, Bone invasion, Muscle invasion & Salivary gland invasion singly or in combination of 3 or 4 in H & E stained sections but no potential prognosticator was identified to be a sufficiently strong indicator of 5 years survival.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have concluded that tumor budding, depth of invasion, and lymphovascular invasion (LVI) are predictors of lymph node metastasis (LNM). In LVI cancer cells invade an endothelium-lined area of vessels [1]. LVI can be seen both 'intratumoral and extratumoral'.…”
Section: Lymphatic and Vascular Invasionmentioning
confidence: 99%
See 1 more Smart Citation